2016
DOI: 10.1002/mds.26552
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term effect of epoetin alfa on clinical and biochemical markers in friedreich ataxia

Abstract: Although results are not in favor of an effect of epoetin alfa in Friedreich ataxia, this is the largest trial testing its effect. It is still possible that epoetin alfa may show some symptomatic effect on upper-limb performance. This study provides class I evidence that erythropoietin does not ameliorate VO2 max in patients with Friedreich ataxia. © 2016 International Parkinson and Movement Disorder Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 34 publications
(46 reference statements)
1
25
0
Order By: Relevance
“…In several cell models, EPO elicited a dose-dependent increase of frataxin [113]. In human disease, randomized controlled trials failed to establish significant changes of frataxin expression or clinical parameters [114, 115]. …”
Section: Therapymentioning
confidence: 99%
“…In several cell models, EPO elicited a dose-dependent increase of frataxin [113]. In human disease, randomized controlled trials failed to establish significant changes of frataxin expression or clinical parameters [114, 115]. …”
Section: Therapymentioning
confidence: 99%
“…The Scale for the Assessment and Rating of Ataxia (SARA) consisting of eight items (gait, stance, sitting, speech disturbance, finger chase, nose‐finger test, fast alternating hand movements, heel‐shin slide) and can score from 0 to 40, with 40 being the worst condition. The scale has been used to score ataxia in several neurological conditions (Bürk et al ., ; Saccà et al ., ; Schmitz‐Hübsch et al ., ).…”
Section: Methodsmentioning
confidence: 99%
“…Only one larger study assessed effect of rhuEPO on FRDA (Saccà et al, 2016). On the basis of their earlier pilot study Saccà et al (2011), tested rhuEPO in 56 patients randomized 1:1 to receive epoetin alfa or placebo.…”
Section: Erythropoietin and Frda: The Bedsidementioning
confidence: 99%
“…Despite being underpowered to show a difference against placebo, few EPO studies reported some clinical benefits (Boesch et al, 2008; Saccà et al, 2016). These findings may be interpreted as results of shorter-term effect of EPO on muscle strength and fitness, which may provide a partial compensation for ataxia.…”
Section: Erythropoietin and Frda: The Bedsidementioning
confidence: 99%